Method for improving performance of bentonite and preparing multicolor coating protective rubber powder by using bentonite

By purifying, modifying and structural adjustment of bentonite, high-performance protective rubber powder is prepared, which solves the problem of limited performance of bentonite and achieves significant performance improvement in the coating industry and excellent performance of colorful coatings.

CN119708902APending Publication Date: 2025-03-28KAIFENG HUIERLIDE BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411787939.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The performance of bentonite in the coating industry is limited and needs to be improved to improve its performance in thickening agents, suspension agents and stabilizers.

Method used

By purifying, modifying and structural adjustment of bentonite, it is converted into compounds such as lithium magnesium silicate, sodium magnesium silicate, potassium magnesium silicate or sodium magnesium aluminum silicate, and is dried, crushed and surface treated to prepare high-performance protective glue powder.

Benefits of technology

It significantly improves the performance of bentonite, and the product performance is 10-20 times, suitable for large-scale industrial production. The prepared protective glue powder shows better water resistance, low addition amount, suspension, stability and construction performance in colorful coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a method for improving the performance of bentonite and a method for preparing multicolor coating protection rubber powder from the bentonite. A method for improving the performance of bentonite and preparing multicolor coating protective rubber powder comprises the following steps: purifying raw ore bentonite to prepare purified bentonite; the purified bentonite is subjected to modification treatment through a chemical combination method, and modified bentonite is prepared; performing structure adjustment on the modified bentonite, and converting the modified bentonite into magnesium lithium silicate, magnesium sodium silicate, magnesium potassium silicate or magnesium aluminum sodium silicate to obtain structure-adjusted bentonite; drying and crushing the structure-adjusted bentonite; carrying out surface treatment on the crushed structure-adjusted bentonite to obtain surface-treated bentonite; and preparing protective rubber powder, and applying the surface treated bentonite to the protective rubber powder of the multicolor paint. The bentonite is purified, modified and structurally adjusted, so that the performance of the bentonite is improved, and the bentonite can be used as protective rubber powder for colorful coatings after viscosity reduction at different stages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a method for improving bentonite performance and preparing multi-colored coating protective rubber powder. Background Art

[0002] Bentonite is an important non-metallic mineral resource with good water and moisture absorption properties. Its main component is montmorillonite, which is a layered silicate mineral with an ideal chemical formula of (Na, Ca) 0.33 (Al,Mg)2[(Si,Al)4O 10 ](OH)2·nH2O, its crystal structure is a 2:1 layered structure consisting of two layers of silicon-oxygen tetrahedron sandwiched by one layer of aluminum-oxygen octahedron. Due to the isomorphous substitution phenomenon, there is a residual negative charge in the montmorillonite layer, which causes the interlayer to adsorb Na + , K + , Ca 2+ Mg 2+ The strong hydration ability of these metal cations leads to the presence of adsorbed water between the montmorillonite layers.

[0003] Bentonite is commonly used as a thickener, suspending agent and stabilizer in the coatings industry due to its good adsorption and swelling properties. However, its performance is limited and needs to be improved. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the performance of bentonite and preparing a multi-color coating protective rubber powder. The performance of bentonite is improved by purifying, modifying and adjusting the structure, and the bentonite can be used for the protective rubber powder of multi-color coatings after reducing the viscosity at different stages.

[0005] In order to achieve the above-mentioned purpose, the present invention provides a method for improving the performance of bentonite and preparing a multi-colored coating protective rubber powder by adopting the following technical scheme:

[0006] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0007] (1) Purification: purifying the raw bentonite to remove impurities and obtain purified bentonite;

[0008] (2) modification, modifying the purified bentonite by a chemical method to obtain modified bentonite;

[0009] (3) structural adjustment, adjusting the structure of the modified bentonite and converting it into lithium magnesium silicate, sodium magnesium silicate, potassium magnesium silicate or sodium magnesium aluminum silicate to obtain structurally adjusted bentonite;

[0010] (4) drying and crushing, drying and crushing the structure-adjusted bentonite;

[0011] (5) surface treatment, performing surface treatment on the crushed structure-adjusted bentonite to obtain surface-treated bentonite;

[0012] (6) Preparing protective rubber powder, and using the surface treated bentonite as protective rubber powder for colorful coatings.

[0013] Preferably, in step (1), raw bentonite is added to distilled water to form a slurry, dispersant A is added and stirred evenly, trifluoroacetic acid is added, the mixture is allowed to stand, the upper layer solution is centrifuged, the supernatant obtained after centrifugation is filtered, and the filter cake is dried to obtain physically purified bentonite.

[0014] Further preferably, the dispersant A is a polyamide polyamine epichlorohydrin polymer or / and a polyurethane polyamine epichlorohydrin polymer, and the mass ratio of the dispersant A to the raw bentonite is 0.1-1%.

[0015] Still more preferably, the polyamide polyamine epichlorohydrin polymer is prepared by the following method: react divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate and zeolite at 140-180° C., cool to 50-55° C., add epichlorohydrin and continue the reaction to obtain the polymer.

[0016] Still more preferably, the polyurethane polyamine epichlorohydrin polymer is prepared by the following method: after reacting divinyl adipate, ethylene glycol, disodium hydrogen phosphate dodecahydrate, triethanolamine and acetone at 50-55° C., epichlorohydrin is added to continue the reaction to obtain the polyurethane polyamine epichlorohydrin polymer.

[0017] Preferably, in step (2), sucrose is dissolved in a sodium acetate solution, heated and stirred until completely dissolved, nitrogen is introduced, allylmalonic acid, boron trifluoride complex and di-tert-butyl peroxide are added to carry out a primary polymerization reaction, and after the reaction is completed, 2-acrylamido-2-methylpropanesulfonic acid is added to carry out a secondary polymerization reaction, and after the reaction is completed, purified bentonite is added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved to obtain the product.

[0018] Further preferably, sucrose is dissolved in a sodium acetate solution with a mass fraction of 2%, heated to 40-45°C and stirred until completely dissolved; at 45-55°C, nitrogen is introduced, allyl malonic acid, boron trifluoride complex and di-tert-butyl peroxide are added for a primary polymerization reaction, and after the reaction is completed, 2-acrylamide-2-methylpropane sulfonic acid is added for a secondary polymerization reaction, and after the reaction is completed, purified bentonite is added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved, so that the mass of the sodium acetate solution is 5-20 times the mass of sucrose, the molar ratio of sucrose to allyl malonic acid is 1:3-3.5, the molar ratio of the boron trifluoride complex and di-tert-butyl peroxide to allyl malonic acid is 0.01-0.1:0.1-0.5:1; the molar ratio of 2-acrylamide-2-methylpropane sulfonic acid to allyl malonic acid is 1-1.3:1.

[0019] Preferably, in step (3), the modified bentonite is subjected to a lithiation, sodium or potassium reaction, oxalic acid and citric acid are added, and after sufficient stirring, the temperature is raised to 25-50° C. while stirring, and the temperature is kept for 10-30 minutes to obtain the modified bentonite; the mass ratio of oxalic acid to citric acid is 1:1; the amount of oxalic acid and citric acid used is 10-20% by mass of the modified bentonite; the reagent for the lithiation reaction is lithium carbonate or butyl lithium; the reagent for the sodium reaction is sodium carbonate or sodium fluoride; and the reagent for the calcification reaction is potassium carbonate.

[0020] Preferably, in step (5), the crushed structure-adjusted bentonite, polyacrylamide, 2-O-adipate monovinyl sucrose ester, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer, water-absorbing resin and water are stirred and mixed at 25-60°C, and then dried and crushed into 200-400 mesh powder to obtain the product; the mass percentages of the structure-adjusted bentonite, polyacrylamide, 2-O-adipate monovinyl sucrose ester, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer and water-absorbing resin are 85-90:1-5:1-5:1-5:1-5:1-5:1-5:1-5 respectively.

[0021] Preferably, in step (6), the protective rubber powder comprises 40-55 parts of deionized water, 5-15 parts of surface-treated bentonite, 1-5 parts of acrylate-ethylene and acrylate-propylene copolymers, and 1-5 parts of hollow glass microspheres.

[0022] Beneficial effects:

[0023] (1) By purifying, modifying and adjusting the structure of bentonite ore, it is converted into compounds such as lithium magnesium silicate, sodium magnesium silicate, potassium magnesium silicate, and sodium magnesium aluminum silicate. This method significantly improves the performance of bentonite through specific processing steps, and the performance of the obtained product is improved by 10-20 times, which is suitable for large-scale industrial production. By compounding viscosity reducers at different stages to reduce its viscosity, it can be used in colorful coatings. When used as protective rubber powder, it has better water resistance, low addition amount, suspension, stability and construction performance.

[0024] (2) The application method is simple and suitable for large-scale industrial production. DETAILED DESCRIPTION

[0025] The present application will be described in detail below in conjunction with embodiments. Each example is provided by way of explanation of the present application but does not limit the present application. In fact, it will be clear to those skilled in the art that modifications and variations may be made in the present application without departing from the scope or spirit of the present application. For example, a feature shown or described as a part of an embodiment may be used in another embodiment to produce yet another embodiment. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention should belong to the scope of protection of the embodiments of the present invention.

[0026] Example 1

[0027] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0028] (1) Purification: add the raw bentonite to distilled water to form a slurry, add dispersant A and stir evenly, then add trifluoroacetic acid, let stand, centrifuge the upper solution, filter the supernatant obtained after centrifugation, and dry the filter cake to obtain physically purified bentonite. Dispersant A is a polyamide polyamine epichlorohydrin polymer, and the mass ratio of dispersant A to raw bentonite is 0.1%; the polyamide polyamine epichlorohydrin polymer is prepared by the following method: react divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate, and zeolite at 140°C, cool to 50°C, add epichlorohydrin and continue to react, and obtain a molar ratio of divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate, zeolite and epichlorohydrin of 2.1:1:1:0.1:1.5.

[0029] (2) Modification: modified bentonite by chemical method to obtain modified bentonite; 50 g sucrose was dissolved in 200 mL sodium acetate solution with a mass fraction of 2%, heated to 40°C and stirred until completely dissolved; nitrogen was introduced at 50°C, allyl malonic acid, boron trifluoride complex and di-tert-butyl peroxide were added to carry out a primary polymerization reaction, after which 2-acrylamide-2-methylpropanesulfonic acid was added to carry out a secondary polymerization reaction, after which purified bentonite was added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved, and the molar ratio of sucrose to allyl malonic acid was 1:3.1, the molar ratio of boron trifluoride complex and di-tert-butyl peroxide to allyl malonic acid was 0.05:0.1:1, and the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to allyl malonic acid was 1.1:1.

[0030] (3) Structural adjustment: structurally adjust the modified bentonite and convert it into lithium magnesium silicate to obtain structurally adjusted bentonite; perform lithiation on the modified bentonite, add oxalic acid and citric acid, stir thoroughly, heat to 30°C while stirring, and keep warm for 10 minutes to obtain; the mass ratio of oxalic acid to citric acid is 1:1; the amount of oxalic acid and citric acid used is 10% of the modified bentonite by mass; the reagent for the lithiation reaction is lithium carbonate.

[0031] (4) Drying and pulverizing: The structure-adjusted bentonite is dried at 60° C. and pulverized to 200 mesh.

[0032] (5) Surface treatment: The crushed structure-adjusted bentonite is surface treated by stirring and mixing the crushed structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer, water-absorbing resin and water at 50° C., and then drying and crushing into 200 mesh powder to obtain a powder; the mass percentages of the structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer and water-absorbing resin are 85:2:3:3:3:2:2, respectively.

[0033] (6) Preparing protective rubber powder, using the surface-treated bentonite as protective rubber powder for multi-color coatings, the protective rubber powder comprises 40 parts of deionized water, 15 parts of the surface-treated bentonite, 5 parts of acrylate-ethylene and acrylate-propylene copolymers, and 5 parts of hollow glass microspheres.

[0034] Example 2

[0035] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0036] Different from Example 1, the reagent for the lithiation reaction is butyl lithium.

[0037] Example 3

[0038] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0039] (1) Purification: add the raw bentonite to distilled water to form a slurry, add dispersant A and stir evenly, then add trifluoroacetic acid, let it stand, centrifuge the upper solution, filter the supernatant obtained after centrifugation, and dry the filter cake to obtain physically purified bentonite. Dispersant A is a polyurethane polyamine epichlorohydrin polymer, and the mass ratio of dispersant A to raw bentonite is 0.5%. Polyurethane polyamine epichlorohydrin polymer is prepared by the following method: react divinyl adipate, ethylene glycol, disodium hydrogen phosphate dodecahydrate, triethanolamine and acetone at 50°C, then add epichlorohydrin to continue the reaction, and obtain a molar ratio of divinyl adipate, ethylene glycol, disodium hydrogen phosphate dodecahydrate, triethanolamine and epichlorohydrin of 1:1.2:0.2:1.6, and the mass ratio of acetone to ethylene glycol is 15.

[0040] (2) Modification: modified bentonite by chemical method to obtain modified bentonite; 40 g sucrose was dissolved in 200 mL sodium acetate solution with a mass fraction of 2%, heated to 45°C and stirred until completely dissolved; nitrogen was introduced at 45°C, allyl malonic acid, boron trifluoride complex and di-tert-butyl peroxide were added to carry out a primary polymerization reaction, after which 2-acrylamide-2-methylpropanesulfonic acid was added to carry out a secondary polymerization reaction, after which purified bentonite was added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved, and the molar ratio of sucrose to allyl malonic acid was 1:3.2, the molar ratio of boron trifluoride complex and di-tert-butyl peroxide to allyl malonic acid was 0.1:0.2:1, and the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to allyl malonic acid was 1.2:1.

[0041] (3) Structural adjustment: structural adjustment is performed on the modified bentonite. The modified bentonite is converted into sodium magnesium by sodium reaction. Oxalic acid and citric acid are added. After sufficient stirring, the temperature is raised to 40°C while stirring. The temperature is kept for 30 minutes to obtain the product. The mass ratio of oxalic acid to citric acid is 1:1. The amount of oxalic acid and citric acid used is 15% of the modified bentonite by mass. The reagent for the sodium reaction is sodium carbonate.

[0042] (4) drying and crushing: drying the structure-adjusted bentonite at 80° C. and crushing it into 200 mesh;

[0043] (5) Surface treatment: The crushed structure-adjusted bentonite is surface treated by stirring and mixing the crushed structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer, water-absorbing resin and water at 40° C., and then drying and crushing into 200 mesh powder to obtain a powder; the mass percentages of the structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer and water-absorbing resin are 88:2:2:2:2:2:2:2, respectively.

[0044] (6) Preparing protective rubber powder, using the surface-treated bentonite as protective rubber powder for colorful coatings, the protective rubber powder comprises 45 parts of deionized water, 10 parts of the surface-treated bentonite, 5 parts of acrylate-ethylene and acrylate-propylene copolymers, and 5 parts of hollow glass microspheres.

[0045] Example 4

[0046] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0047] The difference from Example 3 is that the reagent for the sodiumization reaction is sodium fluoride.

[0048] Example 5

[0049] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0050] (1) Purification: add the raw bentonite to distilled water to form a slurry, add dispersant A and stir evenly, then add trifluoroacetic acid, let stand, centrifuge the upper solution, filter the supernatant obtained after centrifugation, and dry the filter cake to obtain physically purified bentonite. Dispersant A is a polyamide polyamine epichlorohydrin polymer, and the mass ratio of dispersant A to raw bentonite is 1%. The polyamide polyamine epichlorohydrin polymer is prepared by the following method: react divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate, and zeolite at 180°C, cool to 55°C, add epichlorohydrin and continue the reaction to obtain the obtained product. The molar ratio of divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate, zeolite and epichlorohydrin is 2.2:1:1:0.1:2.

[0051] (2) Modification: modified bentonite by chemical method to obtain modified bentonite; 20 g sucrose was dissolved in 200 mL sodium acetate solution with a mass fraction of 2%, heated to 45°C and stirred until completely dissolved; nitrogen was introduced at 55°C, allyl malonic acid, boron trifluoride complex and di-tert-butyl peroxide were added to carry out a primary polymerization reaction, after which 2-acrylamide-2-methylpropanesulfonic acid was added to carry out a secondary polymerization reaction, after which purified bentonite was added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved, and the molar ratio of sucrose to allyl malonic acid was 1:3.5, the molar ratio of boron trifluoride complex and di-tert-butyl peroxide to allyl malonic acid was 0.1:0.5:1, and the molar ratio of 2-acrylamide-2-methylpropanesulfonic acid to allyl malonic acid was 1.3:1.

[0052] (3) Structural adjustment: structurally adjust the modified bentonite and convert it into potassium magnesium silicate to obtain structurally adjusted bentonite; perform potassium reaction on the modified bentonite, add oxalic acid and citric acid, stir thoroughly, heat to 50°C while stirring, and keep warm for 10 to 30 minutes to obtain; the mass ratio of oxalic acid to citric acid is 1:1; the amount of oxalic acid and citric acid used is 20% of the modified bentonite by mass; the reagent for calcification reaction is potassium carbonate.

[0053] (4) drying and crushing: drying the structure-adjusted bentonite at 70° C. and crushing it into 300 mesh;

[0054] (5) Surface treatment: The crushed structure-adjusted bentonite is surface treated by stirring and mixing the crushed structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer, water-absorbing resin and water at 40° C., and then drying and crushing into 300 mesh powder to obtain a powder; the mass percentages of the structure-adjusted bentonite, polyacrylamide, 2-O-monovinyl sucrose adipate, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer and water-absorbing resin are 90:2:2:2:2:1:1, respectively.

[0055] (6) Preparing protective rubber powder, using the surface-treated bentonite as protective rubber powder for colorful coatings, the protective rubber powder comprises 50 parts of deionized water, 15 parts of the surface-treated bentonite, 5 parts of acrylate-ethylene and acrylate-propylene copolymers, and 5 parts of hollow glass microspheres.

[0056] Comparative Example 1

[0057] A method for improving bentonite performance and preparing colorful coating protective rubber powder, comprising the following steps:

[0058] (1) Purification: Dry the raw bentonite.

[0059] (2) Structural adjustment: the original bentonite is structurally adjusted and converted into lithium magnesium silicate to obtain structurally adjusted bentonite; the original bentonite is subjected to lithiation reaction, oxalic acid and citric acid are added, and after sufficient stirring, the temperature is raised to 50°C while stirring, and the temperature is kept for 30 minutes to obtain; the mass ratio of oxalic acid to citric acid is 1:1; the amount of oxalic acid and citric acid used is 20% of the modified bentonite by mass; the reagent for the calcification reaction is lithium carbonate.

[0060] (3) drying and crushing: drying the structure-adjusted bentonite at 70° C. and crushing it into 300 mesh;

[0061] (4) Preparing protective rubber powder, using the crushed structure-adjusted bentonite as protective rubber powder for multi-color coatings, the protective rubber powder comprising 50 parts of deionized water, 15 parts of crushed structure-adjusted bentonite, and 5 parts of pyrophosphate.

[0062] The performance of the bentonite dried and crushed in the above Examples 1-5 and Comparative Example 1 was tested. First, its suspension performance was tested in a 1% distilled water dispersion system and a high-content calcium and magnesium ion water dispersion system (total calcium and magnesium ion concentration was 0-0.01 mol / L).

[0063] Evaluation of suspension performance: Weigh 3.0g of lithium bentonite and disperse it in a 1% distilled water dispersion system and a high-content calcium and magnesium ion water dispersion system (the total concentration of calcium and magnesium ions is 3.42×10-3mol / L, and its configuration method refers to "GB / T1603-2001 Pesticide Emulsion Stability Determination Method"). Stir for 30 minutes at 2000r / min to form a dispersion with a solid content of 1%; then, transfer a certain amount of the dispersion to a 100mL measuring cylinder (to the maximum scale) and let it stand for 24 hours. Observe whether there is stratification or water precipitation in the measuring cylinder.

[0064] Viscosity evaluation: Weigh 13.0g of lithium bentonite and disperse it in 247.0g of distilled water to prepare a dispersion with a solid content of 5%; transfer it to a high-angle beaker, seal it and let it stand for 24 hours at 20°C, and then measure its viscosity (NDJ-8S viscometer, 3# rotor, 60r / min). The results are shown in Table 1.

[0065] Table 1 Suspensibility and viscosity of the products

[0066]

[0067] As shown in Table 1, compared with Comparative Example 1, the amount of clear water precipitated by the crushed structure-adjusted bentonite prepared by the method of the present invention in a 1% distilled water dispersion system and a high-content calcium and magnesium ion water dispersion system after standing for 24 hours is significantly reduced, or even no clear water is precipitated, indicating that the crushed structure-adjusted bentonite prepared by the present invention has excellent suspension performance. The viscosity of the crushed structure-adjusted bentonite prepared by the method of the present invention is not much different from that of Comparative Example 1, indicating that the crushed structure-adjusted bentonite of the present invention retains the gel property.

[0068] Embodiment 6-10

[0069] A multi-color coating comprises a dispersed phase, a protective rubber powder and a continuous phase, wherein the mass ratio of the dispersed phase to the protective rubber solution is 1.5:1:1; the dispersed phase is composed of the following components by mass: 200 parts of water, 10 parts of polyvinyl alcohol, 50 parts of acrylate emulsion, 935 parts of pigment yellow, 6 parts of titanium dioxide, 10 parts of titanium lactate ammonia, 2 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, 1 part of terminal mercaptan-based nitrile rubber, 0.2 parts of ammonium persulfate, 1 part of propylene glycol and 0.2 parts of lauric acid; the continuous phase is composed of the following components by mass: 50 parts of deionized water, 0.1 parts of lauric acid, 2.1 parts of 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, 2.8 parts of titanium dioxide, 60 parts of acrylate and 0.2 parts of ammonium persulfate; wherein the protective rubber powder is prepared according to Examples 1 to 5 respectively; the coating is prepared by mixing the above raw materials.

[0070] Comparative Example 2

[0071] The difference with Examples 6-10 is that the protective rubber powder is prepared according to Comparative Example 1.

[0072] The multi-colored coatings prepared in Examples 6-10 and Comparative Example 2 were characterized according to HG / T 4343-2012. The test results are shown in Table 2.

[0073] Table 2 Characterization of coating properties

[0074]

[0075]

[0076]

[0077] It can be seen from Table 2 that the weather resistance, water resistance, acid and alkali resistance, cold and hot cycle resistance and wear resistance of the colorful coating prepared by the protective rubber powder provided by the present invention all meet the national standard requirements, and its service life and application range are greatly extended.

[0078] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for improving bentonite performance and preparing colorful coating protective rubber powder, characterized in that: The following steps are involved: (1) Purification: purifying the raw bentonite to remove impurities and obtain purified bentonite; (2) modification, modifying the purified bentonite by a chemical method to obtain modified bentonite; (3) structural adjustment, adjusting the structure of the modified bentonite and converting it into lithium magnesium silicate, sodium magnesium silicate, potassium magnesium silicate or sodium magnesium aluminum silicate to obtain structurally adjusted bentonite; (4) drying and crushing, drying and crushing the structure-adjusted bentonite; (5) surface treatment, performing surface treatment on the crushed structure-adjusted bentonite to obtain surface-treated bentonite; (6) Preparing protective rubber powder, and using the surface treated bentonite as protective rubber powder for colorful coatings.

2. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 1, characterized in that: In step (1), raw bentonite is added to distilled water to prepare a slurry, dispersant A is added and stirred evenly, trifluoroacetic acid is added, the mixture is allowed to stand, the upper layer solution is centrifuged, the supernatant obtained after centrifugation is filtered, and the filter cake is dried to obtain physically purified bentonite.

3. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 2, characterized in that: The dispersant A is a polyamide polyamine epichlorohydrin polymer or / and a polyurethane polyamine epichlorohydrin polymer, and the mass ratio of the dispersant A to the original bentonite is 0.1-1%.

4. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 3, characterized in that: The polyamide polyamine epichlorohydrin polymer is prepared by the following method: reacting divinyl adipate, triethylenetetramine, disodium hydrogen phosphate dodecahydrate and zeolite at 140-180° C., cooling to 50-55° C., adding epichlorohydrin and continuing the reaction to obtain the polyamide polyamine epichlorohydrin polymer.

5. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 3, characterized in that: The polyurethane polyamine epichlorohydrin polymer is prepared by the following method: after divinyl adipate, ethylene glycol, disodium hydrogen phosphate dodecahydrate, triethanolamine and acetone are reacted at 50-55° C., epichlorohydrin is added to continue the reaction to obtain the polyurethane polyamine epichlorohydrin polymer.

6. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to any one of claims 1 to 5, characterized in that: In step (2), sucrose is dissolved in a sodium acetate solution, heated and stirred until completely dissolved, nitrogen is introduced, allylmalonic acid, a boron trifluoride complex and di-tert-butyl peroxide are added to carry out a primary polymerization reaction, and after the reaction is completed, 2-acrylamido-2-methylpropanesulfonic acid is added to carry out a secondary polymerization reaction, and after the reaction is completed, purified bentonite is added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved to obtain the product.

7. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 6, characterized in that: The sucrose is dissolved in a sodium acetate solution with a mass fraction of 2%, heated to 40-45° C. and stirred until completely dissolved; at 45-55° C., nitrogen is introduced, allyl malonic acid, a boron trifluoride complex and di-tert-butyl peroxide are added to carry out a primary polymerization reaction, after the reaction is completed, 2-acrylamide-2-methylpropanesulfonic acid is added to carry out a secondary polymerization reaction, after the reaction is completed, purified bentonite is added, stirred, centrifuged to remove the supernatant, washed with distilled water, dried and sieved to obtain a sodium acetate solution with a mass of 5-20 times that of the sucrose, a molar ratio of the sucrose to the allyl malonic acid of 1:3-3.5, a molar ratio of the boron trifluoride complex and the di-tert-butyl peroxide to the allyl malonic acid of 0.01-0.1:0.1-0.5:1; and a molar ratio of the 2-acrylamide-2-methylpropanesulfonic acid to the allyl malonic acid of 1-1.3:

1.

8. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 1, characterized in that: In step (3), the modified bentonite is subjected to a lithiation, sodium or potassium reaction, oxalic acid and citric acid are added, and after sufficient stirring, the temperature is raised to 25-50° C. while stirring, and the temperature is kept for 10-30 minutes to obtain the modified bentonite; the mass ratio of oxalic acid to citric acid is 1:1; the amount of oxalic acid and citric acid used is 10-20% of the modified bentonite by mass; the reagent for the lithiation reaction is lithium carbonate or butyl lithium; the reagent for the sodium reaction is sodium carbonate or sodium fluoride; and the reagent for the calcification reaction is potassium carbonate.

9. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 1, characterized in that: In step (5), the crushed structure-adjusted bentonite, polyacrylamide, 2-O-adipate monovinyl sucrose ester, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer, water-absorbing resin and water are stirred and mixed at 25-60° C., and then dried and crushed into 200-400 mesh powder to obtain the product; the mass percentages of the structure-adjusted bentonite, polyacrylamide, 2-O-adipate monovinyl sucrose ester, chitosan quaternary ammonium salt, dodecyl dimethyl betaine, polyamide polyamine epichlorohydrin polymer and water-absorbing resin are 85-90:1-5:1-5:1-5:1-5:1-5:1-5:1-5 respectively.

10. The method for improving bentonite performance and preparing colorful coating protective rubber powder according to claim 1, characterized in that: In step (6), the protective rubber powder includes 40 to 55 parts of deionized water, 5 to 15 parts of surface-treated bentonite, 1 to 5 parts of acrylate-ethylene and acrylate-propylene copolymers, and 1 to 5 parts of hollow glass microspheres.